Accounting Profession in the Midst of Green Economy Transition: A Literature Review - SURYANATA, I Made Riyan; CAHYANA, I Wayan Windu; CANDRASWARI, Ni Putu Fitria; ERAYANTI, Ni Komang Sri (Journal Management and Hospitality, 2024)
The accounting profession now faces new opportunities and challenges as a result of the shift to a green economy. In addition to producing standard financial statements, accountants must also be able to incorporate sustainability data into reporting and decision-making. Using a descriptive-qualitative approach to the relevant literature, this review seeks to examine the strategic role that the accounting profession plays in promoting a green economy. The study findings suggest that despite the greater need for accountants with sustainability expertise, educational institutions and the business community are still not as prepared as they should be. Key barriers include issues such as lack of professional training, limited coverage of green accounting curricula, and the administrative nature of the accountant’s role. For accountants to contribute strategically to sustainable development, curriculum reform, ongoing training, and organizational culture change are needed. The study highlights the importance of reimagining accountants as a key force behind environmentally and socially conscious corporate practices.